1985
DOI: 10.3177/jnsv.31.533
|View full text |Cite
|
Sign up to set email alerts
|

Effects of aspartame on diabetic rats and diabetic patients.

Abstract: SummaryThe effects of aspartame (L-aspartyl-L-phenylalanine methyl ester) on plasma glucose and insulin levels were investigated in diabetic rats and patients with non-insulin-dependent diabetes mellitus. The oral administration of 0.45mg aspartame per 100g body weight, which is equivalent to 150mg of glucose in sweetness, to streptozotocin-induced diabetic rats had no effect on the plasma glucose or insulin levels . Also, 225mg oral aspartame loading, which is equivalent to 75g of glucose in sweetness, to pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0
1

Year Published

1996
1996
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 2 publications
(2 reference statements)
2
7
0
1
Order By: Relevance
“…Our data confirms previous findings that ASP treatment promotes hyperglycemia and weight gain in hypercholesterolemic zebrafish [2]. The timing of exposure to these food additives appears to be critical in determining the outcome, since it has previously been shown that acute administration of a high dose of ASP to adult diabetic rats had no effect on plasma glucose levels [40]. In our study, exposure commenced in utero via transfer of amino acids through the placenta, and continued during breast-feeding and through to adulthood via the drinking water consumed daily.…”
Section: Discussionsupporting
confidence: 90%
“…Our data confirms previous findings that ASP treatment promotes hyperglycemia and weight gain in hypercholesterolemic zebrafish [2]. The timing of exposure to these food additives appears to be critical in determining the outcome, since it has previously been shown that acute administration of a high dose of ASP to adult diabetic rats had no effect on plasma glucose levels [40]. In our study, exposure commenced in utero via transfer of amino acids through the placenta, and continued during breast-feeding and through to adulthood via the drinking water consumed daily.…”
Section: Discussionsupporting
confidence: 90%
“…Early studies in adults with diabetes did not show acute or chronic effects artificial sweeteners on blood glucose or insulin levels 47, 48 . However, this topic has recently been readdressed as a result of new evidence that artificial sweeteners may be biologically active in the gastrointestinal tract, via binding to sweet taste receptors located on enteroendocrine L-cells 49, 50 .…”
Section: Effects Artificial Sweeteners On Glycemia and Glucoregulatormentioning
confidence: 99%
“…These studies evaluated the effects of aspartame 48-1800 mg in 169 patients with diabetes and 6 healthy subjects, with daily use for 3 days to 18 weeks. 10- 14 Okuno and colleagues 10 investigated the effects of aspartame 125 mg, consumed daily for 2 weeks, on blood glucose, insulin, and glucagon secretion compared with the same values from the week before and the week after the aspartame diet. Nine participants with diabetes received a "jellycake" with aspartame 125 mg daily for 2 weeks.…”
Section: Aspartamementioning
confidence: 99%
“…The patients in both the placebo and aspartame groups experienced similar adverse reactions, including constipation, itching, gastroenteritis, and diarrhea. 13 Shigeta et al 14 evaluated the effects on fasting plasma glucose of diets sweetened with aspartame 24-48 mg for ▲ Sugar substitutes are often used by patients as a means to avoid excess calories and carbohydrates. ▼…”
Section: Aspartamementioning
confidence: 99%